Disability employment quotas: Effects of laws and nudges - Suzanne Duryea; Claudia Martínez Alvear; Raimundo Smith (Inter-American Development Bank (IDB), 2024)
We study the effects of a new 1% employment quota enacted in Chile in 2018 using anonymized administrative data on monthly employer-employee linkages and disability certification records. Our firm-level difference-in-difference results show a 15-20% increase in the number of people with disabilities working in eligible firms after the quota. About a third of the employment effects occur through the relabeling of existing workers as workers with disabilities, and the remainder through new hires. There are no negative effects found for the firms or other workers. We also conducted an experiment in quota-eligible firms to study if firms can be nudged to employ people with disabilities (PwD) by sending letters containing different information. We find that the pure information treatment increased the number of PwD working in the firms and that most of this impact is explained by an increase in the reclassification of incumbent workers. While not transformational for the labor market, inclusion of PwD, quotas and nudges do have an effect.
Keywords: J14; J71; J78; 330; Disability; Disability employment quota; Affirmative ac-tion; Difference-inDifference; RCT